Bimbingan teknis akuntansi keuangan dana desa menggunakan aplikasi Siskeudes - Bakhtiar Abbas; Mahmudin A.S; Jusbair Jusbair; Miswar Rohansyah (DEDIKASI, 2020)
Village fund management has a noble mandate, which is helping the government to realize economic and social justice, but has not been able to run optimally. In addition, the education management of village fund management, especially regarding village financial accounting, is very minimal. Therefore, technical guidance is needed in solving financial management problems in village funds. Targets to be achieved from the technical guidance of village financial accounting, are: (1) Providing knowledge of village fund accounting to village officials to manage village finances. (2) Practicing village fund accounting so that village officials can do it themselves. 3) Prepare the administration of village fund financial reports according to the standard procedures for accountability of village funds. (4) Provides a way to account for village finance funds that are carried out quickly, precisely, accurately and efficiently. (5) Transferring knowledge and accounting knowledge of village funds to village officials so that they can be applied to the reporting of accountability of village funds accurately and accountably. The results that have been achieved are that the apparatus is able to arrange the financial funds of the village through the Siskeudes application system, namely: able to input the realization of village revenue, input the data on the implementation of village finances, input the data disbursement of the Work Implementation Letter to the village treasurer, make SPJ advances in advance payments for activities, input the rest of the remaining downpayments activities, input tax deposit data, input money withdrawal data from the village bank account. Besides being able to print village draft RPJM reports, APBDes, Cash General Cash Books, Village Bank Books and be able to print Reports on Realization of Village Budget and Realization Execution